2023
DOI: 10.1001/jamaoncol.2022.6296
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of Innovative Therapies Across Oncology Practices—Evidence From Immunotherapy

Abstract: ImportanceImmunotherapies reflect an important breakthrough in cancer treatment, substantially improving outcomes for patients with a variety of cancer types, yet little is known about which practices have adopted this novel therapy or the pace of adoption.ObjectiveTo assess adoption of immunotherapies across US oncology practices and examine variation in adoption by practice type.Design, Setting, and ParticipantsThis cohort study used data from Medicare fee-for-service beneficiaries undergoing 6-month chemoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
(83 reference statements)
0
1
0
Order By: Relevance
“…Although this study uncovered a novel approach that can potentially be a treatment for STS, more research is required to establish the use of this novel therapy in children, as molecular mechanisms of STS are similar in both adults and children but precision medicine approach may vary. Moreover, a recent cohort study showed that the adoption of novel therapies in oncology practices that are not part of academic systems was lower in comparison to the practices that were part of academic systems 7 . Hence, more thorough studies exploring this novel drug are required, so that this precision medicine approach can become a standard-of-care regimen for children diagnosed with STS.…”
mentioning
confidence: 99%
“…Although this study uncovered a novel approach that can potentially be a treatment for STS, more research is required to establish the use of this novel therapy in children, as molecular mechanisms of STS are similar in both adults and children but precision medicine approach may vary. Moreover, a recent cohort study showed that the adoption of novel therapies in oncology practices that are not part of academic systems was lower in comparison to the practices that were part of academic systems 7 . Hence, more thorough studies exploring this novel drug are required, so that this precision medicine approach can become a standard-of-care regimen for children diagnosed with STS.…”
mentioning
confidence: 99%